Tomographic prevalence of juxta-apical radiolucency and adjacent structures: a cross-sectional study - Natália Mariane RIGO; Gilson Cesar Nobre FRANCO; Caique Mariano PEDROSO; Thais ALBACH; Adrielli Guimarães FERREIRA; Marcela CLAUDINO; Marcelo Carlos BORTOLUZZI; Amanda Regina FISCHBORN (Universidade Estadual Paulista, 2024)
Abstract Objective The aim of this study was to evaluate juxta-apical radiolucency (JAR) prevalence and its relationship with adjacent structures using cone-beam computed tomography (CBCT). Material and method CBCT scans were analyzed from a database from 2017 to 2021 of adult patients with mandibular third molars to visualize the presence of JAR. Third molars associated with JAR were classified according to impaction depth, angulation, and root development. JAR was also classified according to its relationship with the mandibular canal and its cortical area, size, and location. The chi-square test and the Mann-Whitney Test were performed to compare the age of patients and gender regarding the presence or absence of JAR. Result 1097 CBCT scans were collected from the database during the evaluation period, and after the application of the eligibility criteria, 155 scans were included in the analysis. Thirty-one third molars showed the presence of JAR with a 20% prevalence. Most cases were observed to be unilateral (84%), located mesially (53%), and medium-sized (53%), in contact with the mandibular canal with cortical presence (50%), visualized in third molars mostly mesioangular (36%), partially intraosseous (86%), and with complete root development (92%). No significant differences were detected between gender and age concerning the presence of JAR. Conclusion High JAR prevalence was observed, which was frequently in contact with the mandibular canal, being considered a potential risk for nerve damage.